2018
DOI: 10.1021/acs.orglett.7b03713
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Domino Heck Cyclization/Suzuki Coupling for the Synthesis of 3,3-Disubstituted Oxindoles

Abstract: The first nickel-catalyzed domino Heck cyclization/Suzuki coupling reaction for the synthesis of 3,3-disubstituted oxindoles bearing quaternary all-carbon centers is reported. A wide range of electrophiles, such as aryl iodides, bromides, triflates, and chlorides, are all compatible with the reaction conditions. Moreover, cheap aryl esters, which undergo catalytic C-O bond cleavage, could also be employed as electrophiles. The approach shows good yields and broad scope, complementing a more practical and susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 92 publications
0
45
0
Order By: Relevance
“…In 2018, the Kong group used arylboronic acids as the terminal reagents in a nickel‐catalyzed intramolecular diarylation of alkenes to access 3,3‐disubstituted oxindoles (Scheme 61). [ 131 ] A wide range of electrophiles, such as aryl halides (X = Cl, Br, I) and triflates were compatible with the reaction conditions. Notably, the inexpensive and unreactive aryl esters were also suitable substrates with good yields, providing an alternative method to the conventional palladium‐catalyzed analogues.…”
Section: Intramolecular Dicarbofunctionalization Of Alkenes Via Cyclimentioning
confidence: 99%
“…In 2018, the Kong group used arylboronic acids as the terminal reagents in a nickel‐catalyzed intramolecular diarylation of alkenes to access 3,3‐disubstituted oxindoles (Scheme 61). [ 131 ] A wide range of electrophiles, such as aryl halides (X = Cl, Br, I) and triflates were compatible with the reaction conditions. Notably, the inexpensive and unreactive aryl esters were also suitable substrates with good yields, providing an alternative method to the conventional palladium‐catalyzed analogues.…”
Section: Intramolecular Dicarbofunctionalization Of Alkenes Via Cyclimentioning
confidence: 99%
“…In most cases, the coupling reactions occur in the presence of palladium as a catalyst [8]. Other metals are also used to catalyze the Heck reaction, for example, nickel having many advantages being abundant, non-toxic, and cost effective [9].…”
Section: Introductionmentioning
confidence: 99%
“…[12] In the beginning, reacting 1 a (0.2 mmol) with 2 a (0.26 mmol) by using Pd(OAc) 2 (10 mol %) as a catalyst, PCy 3 (20 mol %) as a ligand, and K 2 CO 3 as a base under an argon atmosphere in MeCN at 80°C led to the formation of the desired 3-phosphinomethyl 3,3-disubstituted oxindole 3 a in 18% yield ( Table 1, entry 1). Among many different approaches to 3,3'-disubstituted oxindoles, palladiumcatalyzed oxidative difunctionalization alkenes in Narylacrylamides provides direct and potentially more efficient access to oxindoles.…”
mentioning
confidence: 99%
“…(Table 1, entry 5). Subsequently, we checked the effect of various bases and found that a serious decrease in the yield was observed using Cs 2 CO 3 , K 3 PO 4 and Et 3 N, indicating that the choice of base was also crucial for the reaction ( Table 1, entries [10][11][12]. Subsequently, we checked the effect of various bases and found that a serious decrease in the yield was observed using Cs 2 CO 3 , K 3 PO 4 and Et 3 N, indicating that the choice of base was also crucial for the reaction ( Table 1, entries [10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation